White phosphorus munitions: pathophysiology, clinical management, and multidisciplinary perspectives on burn injuries and humanitarian challenges - Mingchan Wang; Yaxing Bai; Xiaorui Zhang; Jing Zhang; Along Kang (Frontiers in Public Health, 2025)
White phosphorus (WP), a highly reactive and toxic substance, has been widely used in military applications. White phosphorus munitions (WPMs) embody a complex intersection of military utility and humanitarian concern, inflicting devastating injuries through their dual destructive mechanisms. These weapons induce severe thermal and chemical damage, penetrating deep into tissues to cause progressive necrosis and life-threatening systemic toxicity even with minimal exposure. This review synthesizes current understanding of WP injury pathophysiology—including hypocalcemia-induced arrhythmias, acute respiratory distress syndrome, and hepatorenal failure—while examining evidence-based interventions spanning battlefield first aid to advanced regenerative therapies. By integrating perspectives from military medicine, toxicology, and global health equity, this review provides a comprehensive foundation for clinicians, and researchers confronting the multidimensional challenges posed by WP injuries in conflict and post-conflict settings.